The cricketer's shoulder and injury: Asymmetries in range of movement and muscle length - Benita Olivier; Bhakti Lala; Nadia Gillion (AOSIS, 2020)
Background: Shoulder injuries in cricket are often undetected and untreated. Objectives: To determine whether there are associations between shoulder internal and external rotation range of movement (ROM), throwing arc (TA) ROM, glenohumeral internal rotation deficit (GIRD), external rotation gain (ERG), pectoralis minor muscle length and the incidence of shoulder injury during the first 3 months of a cricket season amongst provincial and club cricketers. Method: Male, actively participating, provincial and club cricketers were included in this prospective longitudinal cohort study. The independent variables included shoulder pain, which did not limit participation in cricket training and matches; shoulder external and internal rotation (ROM, TA ROM, GIRD and ERG) and pectoralis minor muscle length. Time-loss dominant shoulder injury was recorded for 3 months. Results: Nine of the 32 participants sustained dominant shoulder injuries. Initial non-time-loss shoulder pain during baseline testing was associated with time-loss in-season shoulder injury (p = 0.007). Statistically significant side-to-side differences were found for all of the independent variables (internal rotation ROM, TA ROM and pectoralis minor muscle length distance), with the exception of external rotation ROM, amongst the uninjured players. Conclusion: Non-time-loss-defined shoulder pain in actively participating cricketers seems to be a precursor to time-loss shoulder injury. Asymmetries in ROM and pectoralis minor muscle length in uninjured cricketers may have a protective role to play in the case of shoulder injury. Clinical implications: The presence of shoulder pain and asymmetries in ROM should be investigated during the pre-season screening procedures, and early intervention should be implemented where appropriate.